Improved Adsorptive Removal of Reactive Dye with Co-Al Layered Double Hydroxide - Tania (My University, 2023)
Textile industries produce large amounts of toxic chemicals which mostly consist of dyes. the release of such contaminants causes environmental damage and adversely affects human health. Thus, developing an effective adsorbent with low cost and high efficiency is an urgent task. LDH is rich in positive charges and has the potential to act as an efficient adsorbent for the removal of dyes. The present study describes the synthesis of Co-Al layered double hydroxide using a simple co-precipitation method for the adsorption of a textile effluent namely reactive red 120 dye. DLS, Zeta Potential analysis, FESEM, HRTEM, XRD, and XPS were employed to investigate the physicochemical properties of the Co-Al LDH. The XRD pattern exhibited well-defined diffraction peaks, providing evidence for the formation of Co-Al LDH. The irregular circular platelet-like morphology of the Co-Al LDH was confirmed by HRTEM and FESEM techniques. XPS analysis displayed the distinct peaks at 781.2 eV and 797.3 eV corresponding to Co and at 74.1 eV, and 531.4 eV for Al and O, respectively. The adsorption behavior of RR 120 is consistent with the Langmuir adsorption isotherm model and follows the pseudo-second-order kinetic model. Under optimum conditions with a pH of 7.2, the Co- Al LDH exhibits a maximum adsorption capacity of 314 mg/g for the removal of the pollutant. Therefore, the Co-Al LDH demonstrates potential as an effective adsorbent for the mitigation of Reactive Red 120 owing to its straightforward, cost-effective, and environmentally friendly synthesis process.
Keywords: Wastewater Treatment; Reactive Dyes; Adsorption; Layered Double Hydroxides; Emerging Contaminants